Indicadores de violencia intrafamiliar en estudiantes de Enfermería de la Universidad Nacional de Loja - Enríquez Sarango, María Alicia (2023)
Domestic violence refers to a global problem that affects today's society, and contributes to the development of dysfunctional family relationships. The general objective was: Analyze the indicators of domestic violence in students of the Nursing Career of the National University of Loja, to propose actions to prevent domestic violence. Specific objectives: Identify the indicators of domestic violence in students’ Nursing Career and propose actions as a measure for the prevention of domestic violence in students’ Nursing Career. The study was descriptive, quantitative and cross-sectional, the population was consisted of 14 female Nursing students, to obtain the sample the probabilistic method was applied, giving us the number of 14 students; regarding the selection criteria, female students with marital status, married or in a common law union, were taken into consideration. The instrument used was the survey based on the VIFJ4 Domestic Violence Measurement Scale approved and validated in 2014; this includes 25 questions aimed at violence against women in the family environment, distributed in 6 dimensions: physical, psychological, sexual, social, patrimonial and gender violence. The results show psychological violence in 50%, social violence 42.86%, patrimonial violence 42.86% and gender violence 50%, they have a greater impact on the students, behaviors such as: not allowing opinion, insults, infidelity, prohibiting grooming and communicating with other people, facing threats and jealousy, together with not helping with household chores, give a pattern of the inequality of conditions in which the women investigated still live. Given this, it is concluded that domestic violence does not leave immediate visible traces, but its future implications are transcendent and require timely actions